Sodium-ion battery negative electrode active material, preparation method and application thereof

CN122889723APending Publication Date: 2026-10-09BATTEROTECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611158986.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]本发明的主要目的在于提供一种钠离子电池负极活性材料、其制备方法及应用,以解决现有技术中钠离子电池难以兼顾高能量密度和良好循环稳定性的问题

Benefits of technology

[0015]应用本发明的技术方案,通过在硬碳基底中镶嵌过渡金属氧化物纳米颗粒,通过物理限域的方法抑制过渡金属氧化物在充放电过程中的体积变化,在提高负极侧容量的同时,改善了体系的循环稳定性;多孔碳包覆层可以在硬碳基底的基础上进一步约束过渡金属氧化物的体积膨胀,同时可以改善过渡金属氧化物首次效率低和倍率性差的问题。本发明的负极活性材料能够改善体系循环稳定性,同时提高钠离子电池负极侧的比容量,提升体系的能量密度,从而获得高能量密度、长循环寿命的钠离子电池。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889723A_ABST
    Figure CN122889723A_ABST
Patent Text Reader

Abstract

The application provides a sodium ion battery negative electrode active material, a preparation method and application thereof. The material comprises a core and a porous carbon coating layer; the core comprises a hard carbon base and transition metal oxide nanoparticles, and the transition metal oxide nanoparticles are embedded in the inside of the hard carbon base; the transition metal oxide nanoparticles comprise Fe3O4. The application inhibits the volume change of the transition metal oxide in the charging and discharging process through a physical confinement method, improves the cycle stability of the system while improving the capacity of the negative electrode side, and the porous carbon coating layer can further constrain the volume expansion of the transition metal oxide on the basis of the hard carbon base. The negative electrode active material of the application can improve the cycle stability of the system, improve the specific capacity of the negative electrode side of the sodium ion battery, and improve the energy density of the system, so that a sodium ion battery with high energy density and long cycle life is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of secondary battery technology, and more specifically, to a sodium-ion battery negative electrode active material, its preparation method, and its application. Background Technology

[0002] Currently, sodium-ion batteries, as an important supplement to lithium-ion batteries, demonstrate significant cost advantages and resource sustainability in large-scale energy storage. Among them, the NFPP / HC (composite sodium iron phosphate / hard carbon) system exhibits good kinetic performance and cycle stability in extreme cold and heat environments, and has become the mainstream configuration for commercial applications. However, this system has a low energy density. The theoretical specific capacity of NFPP (composite sodium iron phosphate, Na4Fe3(PO4)2P2O7) is 129 mAh / g, but its actual performance in a full cell is only around 100 mAh / g. The anode is usually made of biomass hard carbon, whose specific capacity is typically below 350 mAh / g. Furthermore, considering cost, the capacity of hard carbon used in commercial applications is generally only around 300 mAh / g. The low specific capacity of both the positive and negative electrode materials results in a low energy density for the NFPP / HC system, far lower than the lithium iron phosphate / graphite (144 mAh / g / 350 mAh / g) system used in lithium iron phosphate batteries, making it difficult to meet the demands of high-energy-density energy storage applications.

[0003] Transition metal oxides such as iron oxides are a class of high-capacity anode materials, which can theoretically significantly improve anode capacity. However, these materials are usually accompanied by severe volume expansion during sodium insertion / extraction, which can easily lead to particle pulverization, electrode structure collapse, and excessive electrolyte consumption. This results in rapid capacity decay, low initial coulombic efficiency, and deterioration of rate performance, severely limiting their practical application. Summary of the Invention

[0004] The main objective of this invention is to provide a sodium-ion battery anode active material, its preparation method, and its application, so as to solve the problem that sodium-ion batteries in the prior art are difficult to achieve both high energy density and good cycle stability.

[0005] To achieve the above objectives, according to one aspect of the present invention, a sodium-ion battery anode active material is provided, comprising a core and a porous carbon coating layer covering the surface of the core; the core comprises a hard carbon substrate and transition metal oxide nanoparticles, wherein the transition metal oxide nanoparticles are embedded inside the hard carbon substrate; wherein the transition metal oxide nanoparticles comprise Fe3O4.

[0006] Furthermore, the particle size Dv50 of the transition metal oxide nanoparticles is 10~50 nm; and / or the transition metal oxide nanoparticles include a mixture of Fe2O3 and Fe3O4, with a weight ratio of Fe2O3 to Fe3O4 of (0.2~0.6):1.

[0007] Furthermore, the porous carbon coating layer is obtained by coating with a chain-like polymer; preferably, the chain-like polymer includes polyaniline and / or polyacrylic acid, with a weight-average molecular weight of 10,000 to 1,000,000; and / or the specific surface area of ​​the sodium-ion battery negative electrode active material is ≤100 m². 2 / g; and / or the pore volume of the sodium-ion battery negative electrode active material is ≤0.3cm³. 3 / g.

[0008] Furthermore, the weight ratio of transition metal oxide nanoparticles to hard carbon substrate is (0.1~0.5):1; and / or the thickness of the porous carbon coating layer is 1~10 nm.

[0009] Furthermore, the hard carbon substrate material includes resin-based hard carbon with a discharge specific capacity of 340~360 mAh / g.

[0010] According to another aspect of the present invention, a method for preparing the above-mentioned sodium-ion battery negative electrode active material is provided, comprising the following steps: Step S1, mixing hard carbon raw material and transition metal oxide nanoparticles and stirring to obtain an intermediate; the stirring time is 30~60 min and the stirring speed is 300~500 r / min; Step S2, mixing the intermediate with an aqueous solution of a chain polymer and carbonizing it in an inert gas atmosphere to obtain the sodium-ion battery negative electrode active material.

[0011] Further, in step S1, the weight ratio of transition metal oxide nanoparticles to hard carbon raw material is (0.1~0.5):1.

[0012] Further, in step S2, the weight ratio of the chain polymer to the intermediate is (0.005~0.2):1; and / or the inert gas includes Ar and / or N2; and / or the carbonization temperature is 1000~1300℃, and the time is 2~5h.

[0013] According to another aspect of the present invention, a sodium-ion battery negative electrode sheet is provided, comprising a negative electrode current collector and a negative electrode material active layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode material active layer comprises the aforementioned sodium-ion battery negative electrode active material.

[0014] According to another aspect of the present invention, a sodium-ion battery is provided, comprising the sodium-ion battery negative electrode sheet described above.

[0015] By embedding transition metal oxide nanoparticles in a hard carbon substrate, the volume change of transition metal oxides during charge and discharge is suppressed through physical confinement, thereby improving both the negative electrode capacity and the cycle stability of the system. The porous carbon coating further constrains the volume expansion of the transition metal oxides on top of the hard carbon substrate, and also improves the problems of low initial efficiency and poor rate performance of transition metal oxides. The negative electrode active material of this invention can improve the cycle stability of the system, increase the specific capacity of the sodium-ion battery negative electrode, and enhance the energy density of the system, thus obtaining a sodium-ion battery with high energy density and long cycle life. Attached Figure Description

[0016] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0017] Figure 1 A schematic diagram of the structure of the sodium-ion battery negative electrode active material according to Embodiment 1 of the present invention is shown;

[0018] Figure 2 The cycle performance curve of the sodium-ion battery according to Example 1 of the present invention is shown.

[0019] The above figures include the following reference numerals:

[0020] 1. Hard carbon substrate; 2. Transition metal oxide nanoparticles; 3. Porous carbon coating layer. Detailed Implementation

[0021] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.

[0022] As described in the background section of this invention, existing technologies for sodium-ion batteries suffer from the problem of simultaneously achieving high energy density and good cycle stability. To address this issue, in a typical embodiment of this invention, a sodium-ion battery anode active material is provided, comprising a core and a porous carbon coating layer on the surface of the core; the core comprises a hard carbon substrate and transition metal oxide nanoparticles, the transition metal oxide nanoparticles being embedded within the hard carbon substrate; wherein the transition metal oxide nanoparticles include Fe3O4.

[0023] Iron oxides are a class of high-capacity anode materials, but they suffer from problems such as large volume expansion, low initial efficiency, and poor rate performance, making them difficult to apply directly in sodium-ion batteries. This invention physically confines high-capacity transition metal oxide nanoparticles within the porous structure of a hard carbon substrate, utilizing the conductive network and structural buffering effect of hard carbon to suppress the volume expansion and aggregation of the transition metal oxide nanoparticles. Furthermore, a network of porous carbon coating is applied to the core surface to synergistically enhance interface stability, reduce ion diffusion resistance, and improve initial efficiency and rate performance.

[0024] Hard carbon is an amorphous carbon material obtained by carbonizing, structurally regulating, and surface modifying carbon-containing precursors such as biomass, resin, and coal tar pitch. Its crystal structure exhibits short-range order and long-range disorder, possessing abundant sodium storage sites, making it the most commonly used anode material in sodium-ion batteries. Transition metal oxides are a class of high-capacity anode materials that can undergo conversion or intercalation reactions with sodium ions. The theoretical specific capacity of Fe2O3 is 1007 mAh / g, and that of Fe3O4 is 926 mAh / g, significantly higher than commonly used hard carbon anodes (≤350 mAh / g). The difference between Fe2O3 and Fe3O4 lies in the fact that Fe2O3 is a semiconductor material with low intrinsic conductivity and poor kinetics; while Fe3O4's crystal structure contains Fe... 2+ and Fe 3+ Electrons can conduct between iron ions in different valence states, exhibiting half-metallic properties. Its conductivity is much higher than that of Fe2O3, resulting in lower impedance and faster reaction kinetics.

[0025] This invention utilizes transition metal oxide nanoparticles because the bulk Fe3O4 has a high volume expansion rate. Transforming the bulk phase into a nanophase effectively reduces ionic and electronic impedance while improving the volume expansion effect. The Fe3O4-containing nanoparticles, embedded in the porous structure of a hard carbon substrate, serve as the primary sodium storage site and high-capacity active centers, significantly enhancing the theoretical capacity of the anode. Furthermore, the embedding of the Fe3O4-containing nanoparticles physically confines them within the pores of the hard carbon substrate, creating spatial constraints that significantly reduce pulverization and SEI breakdown caused by volume expansion, thus improving cycle stability.

[0026] The porous carbon coating layer is a layer of porous carbon material with a network cross-linking on the core surface. It can reduce the diffusion resistance of sodium ions at the interface, improve the interface stability, reduce the side reactions between the negative electrode active material and the electrolyte, and the network cross-linking structure can also suppress the volume expansion of iron oxide during charging. It has the functions of flexible buffer and ion transport channel. It works together with the hard carbon substrate to suppress the expansion of Fe3O4 while reducing the interface impedance, significantly improving the first coulombic efficiency and rate performance.

[0027] In the negative electrode active material of this invention, the hard carbon substrate provides the main sodium ion insertion / extraction sites, serving as the physical carrier for the transition metal oxide nanoparticles and maintaining the overall structural integrity. The transition metal oxide nanoparticles, as the high-capacity sodium storage host, participate in the conversion reaction, significantly improving the overall specific capacity. Nano-sizing further reduces diffusion resistance. A porous carbon coating layer covers the outer surface of the core, forming a physical constraint layer that suppresses the volume expansion of the transition metal oxide nanoparticles during charging and discharging, while reducing interfacial side reactions and improving initial coulombic efficiency and rate performance. In summary, in the negative electrode active material of this invention, the hard carbon substrate provides the conductive network and confined space, the transition metal oxide nanoparticles provide high capacity, and the porous carbon coating layer provides mechanical constraint and interfacial protection. The synergistic effect of these three elements significantly improves the cycle stability of the system, greatly increases the specific capacity of the sodium-ion battery's negative electrode side, and enhances the system's energy density, thereby obtaining a sodium-ion battery with high energy density and long cycle life.

[0028] In a preferred embodiment, the transition metal oxide nanoparticles have a particle size Dv50 of 10-50 nm; and / or the transition metal oxide nanoparticles include a mixture of Fe2O3 and Fe3O4, with a weight ratio of Fe2O3 to Fe3O4 of (0.2-0.6):1. Controlling the Dv50 of the transition metal oxide nanoparticles within the above range is preferable, as it facilitates more complete embedding into the pores of the hard carbon substrate and maintains the integrity of the material structure by dispersing stress, while also preventing agglomeration and thus ensuring high utilization of active sites. Fe3O4 can be used alone or in combination with Fe2O3. Fe2O3 has high capacity, while Fe3O4 has good rate performance; combining them balances their advantages, enabling the nanoparticles to achieve efficient synergistic sodium storage within a confined space, significantly improving the initial coulombic efficiency and cycle stability.

[0029] Continuous, cross-linked network structures can enhance mechanical toughness and volume buffering capacity. In a preferred embodiment, the porous carbon coating layer is obtained by coating with a chain-like polymer; preferably, the chain-like polymer includes polyaniline and / or polyacrylic acid, with a weight-average molecular weight of 10,000 to 1,000,000; and / or the specific surface area of ​​the sodium-ion battery negative electrode active material is ≤100 m². 2 / g and / or the pore volume of the sodium-ion battery negative electrode active material is ≤0.3cm³. 3 / g. The above conditions indicate that the porous carbon coating layer of the sodium-ion battery anode active material possesses both density and appropriate porosity, effectively blocking electrolyte penetration and suppressing side reactions while retaining Na+. + A fast transport channel, while balancing mechanical constraints and ion diffusion dynamics, enables the coating layer to have both flexible protection and efficient transport functions, achieving a balance between high capacity and long cycle life.

[0030] In a preferred embodiment, the weight ratio of transition metal oxide nanoparticles to a hard carbon substrate is (0.1~0.5):1, preferably (0.25~0.35):1; and / or the thickness of the porous carbon coating layer is 1~10 nm. The content of transition metal oxide nanoparticles within the above range is preferable, as this allows the negative electrode active material to provide higher capacity while maintaining good cycle stability, achieving a balance between capacity improvement and cycle stability. These conditions are beneficial for further improving the negative electrode capacity while maintaining the structural integrity and conductive network continuity of the hard carbon substrate. The thickness of the porous carbon coating layer is preferably controlled within the above range, resulting in more complete coating without excessively affecting high-temperature stability. The above thickness range can match the size of the transition metal oxide nanoparticles, forming a uniform, dense, and elastic interface layer, synergistically suppressing volume expansion and stabilizing the SEI film, enabling the negative electrode active material to possess both high capacity, high initial coulombic efficiency, and long cycling performance.

[0031] Compared to biomass hard carbon, resin-based hard carbon provides more sodium ion intercalation sites and a more stable conductive network, significantly improving the capacity contribution of the hard carbon substrate. In a preferred embodiment, the hard carbon substrate material includes resin-based hard carbon with a discharge specific capacity of 340~360 mAh / g. It has a highly ordered microcrystalline region and a uniform nanoporous structure. The resin-based raw material has strong controllability, and the pore size distribution is concentrated after carbonization, which is beneficial for the intercalation and confinement of transition metal oxide nanoparticles. The high-capacity hard carbon substrate can also synergistically enhance the total capacity of the anode with the help of transition metal oxide nanoparticles. At the same time, its excellent structural integrity can effectively buffer the expansion of transition metal oxides and reduce interfacial stress. In addition, the high specific capacity hard carbon substrate can reduce the proportion of transition metal oxide nanoparticles added, further optimizing cycle stability while maintaining high energy density.

[0032] In another typical embodiment of the present invention, a method for preparing the above-mentioned sodium-ion battery negative electrode active material is also provided, comprising the following steps: Step S1, mixing hard carbon raw material and transition metal oxide nanoparticles and stirring to obtain an intermediate; the stirring time is 30~60min and the stirring speed is 300~500r / min; Step S2, mixing the intermediate with an aqueous solution of a chain polymer and carbonizing it in an inert gas atmosphere to obtain the sodium-ion battery negative electrode active material.

[0033] First, hard carbon raw materials and transition metal oxide nanoparticles are stirred at low speed for an extended period to ensure uniform spatial distribution of the two materials. This allows the nanoparticles to be uniformly embedded in the hard carbon channels, preventing agglomeration and improving the confinement effect, resulting in an intermediate. The intermediate is then mixed with a chain-like polymer and carbonized in an inert gas atmosphere, causing it to uniformly coat the core surface and form a continuous porous carbon shell. This preparation method is simple, easy to operate, and suitable for industrial production. The resulting sodium-ion battery anode active material achieves both high energy density and high cycle stability.

[0034] In a preferred embodiment, in step S1, the weight ratio of transition metal oxide nanoparticles to hard carbon raw material is (0.1~0.5):1, preferably (0.25~0.35):1. These conditions facilitate more complete embedding of the transition metal oxide nanoparticles into the microporous structure of the hard carbon substrate without inducing oxidation or agglomeration, resulting in uniform loading of the negative electrode active material, continuous conductive network, and significantly improved initial coulombic efficiency and cycle stability.

[0035] To further improve the thickness uniformity of the porous carbon coating layer, so as to more fully suppress expansion and side reactions and promote Na + In a preferred embodiment, for the purpose of transport, in step S2, the weight ratio of the chain polymer to the intermediate is (0.005~0.2):1; and / or the inert gas includes Ar and / or N2; and / or the carbonization temperature is 1000~1300℃, and the time is 2~5h. Under these conditions, it is beneficial to promote the more complete conversion of the chain polymer into a network of porous carbon, retain the pore structure and form a conductive network, so that the coating layer has the functions of mechanical buffering, ion channels and interface stabilization, achieving a balance between high capacity and long lifetime.

[0036] In another typical embodiment of the present invention, a sodium-ion battery negative electrode sheet is also provided, including a negative electrode current collector and a negative electrode material active layer disposed on at least one side of the negative electrode current collector. The negative electrode material active layer includes the sodium-ion battery negative electrode active material described above in the present invention, which has significantly improved energy density and has a high cycle capacity retention rate.

[0037] In another typical embodiment of the present invention, a sodium-ion battery is also provided, including the sodium-ion battery negative electrode sheet described above, which has high energy density and long cycle life. The positive electrode of the sodium-ion battery can be an NFPP system, or it can be extended to a transition metal oxide system, as well as a Prussian blue system and a Prussian white system.

[0038] The preparation method of sodium-ion batteries can employ conventional methods in the art. Exemplarily, in some embodiments, the preparation method of sodium-ion batteries includes the following steps:

[0039] Step B1: NFPP, conductive agent (conductive carbon black), binder (PVDF), dispersant (amide-based dispersant), and carbon nanotubes (CNTs) are uniformly mixed, and an appropriate amount of solvent (NMP) is added. The mixture is stirred until homogeneous to obtain the positive electrode slurry. The positive electrode slurry is coated onto carbon-coated aluminum foil and dried to obtain the positive electrode sheet. The material ratios can be adjusted as needed. Typically, the mixing ratio of NFPP is >90%, the mixing ratio of binder is ≤3%, and the mixing ratio of dispersant is ≤0.3%. The solid content of the positive electrode slurry is usually 50-80%. The areal density of the positive electrode can be dynamically adjusted according to the battery design, typically 100-300 g / m³. 2 .

[0040] Step B2: The negative electrode active material is uniformly mixed with the conductive agent (conductive carbon black), CMC (carboxymethyl cellulose), PAA (polyacrylic acid), and SBR (styrene-butadiene rubber). An appropriate amount of solvent (deionized water) is added and stirred until homogeneous to obtain the negative electrode slurry. The negative electrode slurry is then coated onto aluminum foil and dried to obtain the negative electrode sheet. The material ratio can be changed as needed; typically, the mixing ratio of the negative electrode active material is greater than 90%, and the solid content of the negative electrode slurry is usually 40-60%. The negative electrode areal density is calculated from the positive electrode areal density and the NP ratio, which is typically taken as 1.1-1.5.

[0041] Step B3 involves rolling the obtained positive and negative electrode sheets separately. The compaction density of the electrodes can be dynamically adjusted according to the battery design. Typically, the compaction density of the positive electrode sheet ranges from 2.0 to 3.0 g / cm³. 3 The compaction density of the negative electrode sheet ranges from 0.9 to 1.1 g / cm³. 3 .

[0042] Step B4: Cut the rolled positive and negative electrode sheets to appropriate sizes, with the positive electrode sheet slightly smaller than the negative electrode sheet. Stack them in the order of separator / negative electrode / [separator / positive electrode / separator / negative electrode]n / separator (n is the number of repeating units; the larger the value of n, the higher the battery capacity, which can be adjusted as needed). Encapsulate the outside with an aluminum-plastic film. After assembly, weld tabs onto the positive and negative electrodes respectively.

[0043] Step B5: After the battery is assembled, place it in a vacuum oven at 100-120°C for 12-24 hours to remove moisture from the positive and negative electrodes, and seal the battery after electrolyte filling. Conventional sodium-ion battery electrolyte can be used.

[0044] Step B6: After the battery has aged, formed, and been tested for capacity (50% SOC), a sodium-ion battery is obtained.

[0045] Typical, but not limiting, transition metal oxide nanoparticles have a particle size Dv50 of 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, or any two of these values.

[0046] Typically, but not limitingly, when transition metal oxide nanoparticles comprise a mixture of Fe2O3 and Fe3O4, the weight ratio of Fe2O3 to Fe3O4 is 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, or any two of these values.

[0047] Typical, but not limiting, weight ratios of transition metal oxide nanoparticles to hard carbon substrates are 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.28:1, 0.30:1, 0.32:1, 0.35:1, 0.4:1, 0.45:1, 0.5:1, or any two of these values.

[0048] Typical, but not limiting, thicknesses of porous carbon coatings are 1 nm, 2 nm, 5 nm, 8 nm, 10 nm, or any two of these values.

[0049] Typically, but not limitingly, in step S2, the carbonization temperature is 1000℃, 1050℃, 1100℃, 1150℃, 1200℃, 1250℃, 1300℃ or any two of these values; the carbonization time is 2h, 3h, 3.5h, 4h, 5h or any two of these values.

[0050] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.

[0051] Example 1

[0052] Step S1: Hard carbon raw material and transition metal oxide nanoparticles (Fe3O4, Dv50 20nm) are mixed at a weight ratio of 0.33:1 to ensure a 0.33:1 weight ratio between the transition metal oxide nanoparticles and the hard carbon substrate. The mixture is then stirred at a low speed for 40 minutes at a stirring speed of 400 r / min to obtain an intermediate. The hard carbon raw material can have a discharge specific capacity of 350 mAh·g. -1 Resin-based hard carbon.

[0053] Step S2: The intermediate is mixed with a deionized aqueous solution of a chain polymer (polyaniline, weight average molecular weight of 500,000) to a weight ratio of chain polymer to intermediate of 0.05:1. Then, carbonization is carried out in an argon atmosphere at a temperature of 1200℃ for 3 hours to obtain a sodium-ion battery anode active material with a specific surface area <100 m². 2 / g, pore volume <0.3cm³ 3 / g, the thickness of the porous carbon coating is 5nm.

[0054] Examples 2 to 3

[0055] The difference from Example 1 is that the weight ratio of transition metal oxide nanoparticles to hard carbon substrate is different, as detailed in Table 1.

[0056] Examples 4 to 5

[0057] The difference from Example 1 is that the weight ratio of the chain polymer compound to the intermediate is different, as detailed in Table 1.

[0058] Example 6

[0059] The difference from Example 1 is that the types of transition metal oxide nanoparticles are different, as detailed in Table 1.

[0060] Example 7

[0061] The difference from Example 1 is that the types of chain polymers are different, as detailed in Table 1.

[0062] Comparative Example 1

[0063] The difference from Example 1 is that no transition metal oxide nanoparticles and chain polymer materials were added.

[0064] Comparative Example 2

[0065] The difference from Example 1 is that no transition metal oxide nanoparticles were added.

[0066] Comparative Example 3

[0067] The difference from Example 1 is that no chain polymer material was added.

[0068] Performance testing:

[0069] The negative electrode active materials prepared in the above embodiments and comparative examples were analyzed and tested as follows, and the results are shown in Table 1.

[0070] 1. Negative electrode active material

[0071] Particle size Dv50 of transition metal oxide nanoparticles: GB / T 19077-2024, particle size analysis by laser diffraction.

[0072] Specific surface area of ​​anode active materials for sodium-ion batteries: GB / T 19587-2017, determination of specific surface area of ​​solid materials by gas adsorption BET method.

[0073] Pore ​​volume of sodium-ion battery anode active material: Micron ASAP2460 fully automated specific surface area and porosity analyzer (BET), adsorbed gas N2@77K, and NLDFT model was used to fit the isothermal adsorption-desorption curves.

[0074] Thickness of the porous carbon coating: observed by transmission electron microscopy (TEM).

[0075] 2. Electrochemical performance

[0076] Sodium-ion batteries were prepared according to the following method:

[0077] Step B1: NFPP, conductive agent (conductive carbon black), binder (PVDF), dispersant (amide dispersant), and carbon nanotubes (CNTs) are uniformly mixed at a mass ratio of 96.1:1.2:2.0:0.1:0.6. An appropriate amount of solvent (NMP) is added, and the mixture is stirred until homogeneous to obtain a positive electrode slurry with a solid content of 70%. The positive electrode slurry is coated onto carbon-coated aluminum foil and dried to obtain a positive electrode sheet. The areal density of the positive electrode is 150 g / m³. 2 .

[0078] Step B2: The negative electrode active material, conductive agent (conductive carbon black), CMC (carboxymethyl cellulose), PAA (polyacrylic acid), and SBR (styrene-butadiene rubber) are uniformly mixed at a mass ratio of 95.8:1.0:0.7:1.0:1.5. An appropriate amount of solvent (deionized water) is added and stirred evenly to obtain a negative electrode slurry with a solid content of 50%. The negative electrode slurry is coated onto aluminum foil and dried to obtain a negative electrode sheet. The negative electrode areal density is calculated from the positive electrode areal density and the NP ratio, with the NP ratio taken as 1.15.

[0079] Step B3 involves rolling the obtained positive and negative electrode sheets separately to achieve a compaction density of 2.2 g / cm³ for the positive electrode sheet. 3 The compaction density of the negative electrode sheet reaches 0.95 g / cm³. 3 .

[0080] Step B4: Cut the rolled positive and negative electrode sheets to appropriate sizes, with the positive electrode sheet slightly smaller than the negative electrode sheet. Stack them in the order of separator / negative electrode / [separator / positive electrode / separator / negative electrode]n / separator (n=10). Encapsulate the outside with aluminum-plastic film. After assembly, weld tabs onto the positive and negative electrodes respectively.

[0081] Step B5: After the battery is assembled, place it in a vacuum oven at 105°C for 18 hours to remove moisture from the positive and negative electrodes, and seal the battery after electrolyte injection.

[0082] Step B6: After the battery has aged, formed, and been tested (50% SOC), the sodium-ion battery to be tested is obtained.

[0083] 2.1 Negative electrode side capacity

[0084] The negative electrode capacity is provided by both the hard carbon substrate and the transition metal oxide nanoparticles. The negative electrode capacity = the specific capacity of the hard carbon substrate × the proportion of the hard carbon substrate + the specific capacity of the transition metal oxide nanoparticles × the proportion of the transition metal oxide nanoparticles.

[0085] 2.2 Cyclic Performance

[0086] The 45℃ cycling performance test steps are as follows: 1) Rest for 10 min; 2) 0.33C DC to 1.5V; 3) Rest for 10 min; 4) 0.33C CC to 3.6V, CV to 0.05C; 5) Rest for 10 min; 6) 0.33C DC to 1.5V; 7) Rest for 10 min; 8) 1C CC to 3.6V, CV to 0.05C; 9) Rest for 10 min; 10) 1C DC to 1.5V; 11) Rest for 10 min; 12) Cycles 8-11, 100 CLS; 13) 0.33C CC to 3.6V, CV to 0.05C; 14) Rest for 10 min; 15) 0.33C DC to 1.5V; 16) Rest for 10 min. min; 17) loop 8) to 16), 100CLS; 18) END.

[0087] Table 1

[0088]

[0089] A schematic diagram of the structure of the sodium-ion battery negative electrode active material in Example 1 is shown below. Figure 1 As can be seen, the sodium-ion battery anode active material includes a core and a porous carbon coating layer 3 covering the surface of the core. The core includes a hard carbon substrate 1 and transition metal oxide nanoparticles 2 embedded therein. The cycle performance curve of the sodium-ion battery in Example 1 is shown in [reference needed]. Figure 2 It can be seen that after 1000 cycles at 45℃ and 1C / 1C, the capacity retention rate is still greater than 98%, indicating good cycle stability.

[0090] As can be seen, Comparative Example 1, lacking the addition of transition metal oxide nanoparticles and porous carbon coating, exhibits low negative electrode capacity, consequently affecting the energy density and cycle stability of the entire battery system. Comparative Example 2, by coating the hard carbon material with porous carbon and constructing continuous electron transport pathways on the surface of the hard carbon particles, only partially improves cycle performance, with capacity remaining low. Comparative Example 3 embeds transition metal oxide nanoparticles within the hard carbon channels, suppressing volume changes during charge and discharge through physical confinement. This improves both negative electrode capacity and cycle stability to some extent; however, the lack of a porous carbon coating layer to synergistically constrain the volume expansion of the transition metal oxides limits the improvement in cycle performance. Compared to the comparative examples, the embodiments of this invention embed transition metal oxide nanoparticles within the hard carbon particle channels and perform porous carbon coating externally. The synergistic conductive network and physical confinement result in significantly superior capacity performance and cycle stability compared to the comparative examples.

[0091] As can be seen from the above, this invention, by embedding transition metal oxide nanoparticles in a hard carbon substrate, suppresses the volume change of transition metal oxides during charge and discharge through physical confinement, thereby improving the capacity on the negative electrode side and enhancing the cycle stability of the system. The porous carbon coating layer can further constrain the volume expansion of transition metal oxides on the basis of the hard carbon substrate, and can also improve the problems of low initial efficiency and poor rate performance of transition metal oxides. The negative electrode active material of this invention can significantly improve the cycle stability of the system, while greatly increasing the specific capacity on the negative electrode side of the sodium-ion battery, improving the energy density of the system, and thus obtaining a sodium-ion battery with high energy density and long cycle life.

[0092] Furthermore, it can be seen that the overall effect is better when all process parameters are within the preferred range of the present invention.

[0093] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A sodium-ion battery negative electrode active material, characterized in that, Includes a core and a porous carbon coating layer covering the surface of the core; The core comprises a hard carbon substrate and transition metal oxide nanoparticles, wherein the transition metal oxide nanoparticles are embedded within the hard carbon substrate. The transition metal oxide nanoparticles include Fe3O4.

2. The sodium-ion battery negative electrode active material according to claim 1, characterized in that, The particle size Dv50 of the transition metal oxide nanoparticles is 10~50 nm; and / or The transition metal oxide nanoparticles comprise a mixture of Fe2O3 and Fe3O4, with a weight ratio of Fe2O3 to Fe3O4 of (0.2~0.6):

1.

3. The sodium-ion battery negative electrode active material according to claim 1 or 2, characterized in that, The porous carbon coating layer is obtained by coating with a chain-like polymer; preferably, the chain-like polymer includes polyaniline and / or polyacrylic acid, with a weight-average molecular weight of 10,000 to 1,000,000; and / or The specific surface area of ​​the sodium-ion battery negative electrode active material is ≤100m². 2 / g; and / or The pore volume of the sodium-ion battery negative electrode active material is ≤0.3 cm³. 3 / g.

4. The sodium-ion battery negative electrode active material according to any one of claims 1 to 3, characterized in that, The weight ratio of the transition metal oxide nanoparticles to the hard carbon substrate is (0.1~0.5):1; and / or The thickness of the porous carbon coating layer is 1~10 nm.

5. The sodium-ion battery negative electrode active material according to any one of claims 1 to 4, characterized in that, The hard carbon substrate is made of resin-based hard carbon with a discharge specific capacity of 340~360 mAh / g.

6. The method for preparing the sodium-ion battery negative electrode active material according to any one of claims 1 to 5, characterized in that, Includes the following steps: Step S1: Mix hard carbon raw material and transition metal oxide nanoparticles and stir to obtain an intermediate; the stirring time is 30-60 min and the stirring speed is 300-500 r / min. Step S2: The intermediate is mixed with an aqueous solution of a chain polymer and carbonized in an inert gas atmosphere to obtain the sodium-ion battery negative electrode active material.

7. The method for preparing the sodium-ion battery negative electrode active material according to claim 6, characterized in that, In step S1, the weight ratio of the transition metal oxide nanoparticles to the hard carbon raw material is (0.1~0.5):

1.

8. The method for preparing the sodium-ion battery negative electrode active material according to claim 6 or 7, characterized in that, In step S2 The weight ratio of the chain polymer to the intermediate is (0.005~0.2):1; and / or The inert gas includes Ar and / or N2; and / or The carbonization temperature is 1000~1300℃, and the time is 2~5h.

9. A sodium-ion battery negative electrode sheet, comprising a negative electrode current collector and a negative electrode material active layer disposed on at least one side of the negative electrode current collector, characterized in that, The negative electrode material active layer comprises the sodium-ion battery negative electrode active material according to any one of claims 1 to 5.

10. A sodium-ion battery, characterized in that, Includes the sodium-ion battery negative electrode sheet as described in claim 9.